The impact of acute morning versus evening high-intensity interval training on circulating irisin levels and metabolic parameters in overweight postmenopausal women - Akram Jafari; Fariba Kazemi (Experimental Gerontology, 2025)
Purpose of the research: Exercise is considered beneficial for postmenopausal women to manage weight and improve metabolism, but research on the impact of exercise timing on irisin levels and metabolic health in overweight postmenopausal women is inconclusive. This study aims to compare the effects of acute morning and evening high-intensity interval training (HIIT) on irisin levels and metabolic parameters in overweight postmenopausal women. Methods: Fifty-two overweight postmenopausal women aged 53.91 ± 2.71 years were randomly assigned to HIIT (n = 28) and control (n = 24) groups. The HIIT group performed 20 min of repeated 8-second cycling sprints interspersed with 12-second rest intervals at 08:00 and 18:00, with at least 36 h of recovery between sessions, in a randomized order. Blood samples were collected 5 min before, and 5 and 120 min after exercise. Result: Significant within-group increases in irisin (p < 0.01), insulin (p < 0.01), and glucose (p < 0.05) were observed following HIIT. A main effect of time of day revealed higher irisin concentrations in the evening (p < 0.01), although no significant interaction was found between exercise timing and group. No between-group differences in area under the curve (AUC) for irisin or insulin were detected. Conclusions: Acute HIIT elicited favorable changes in irisin and metabolic markers regardless of time of day. Irisin levels increased significantly after HIIT in both morning and evening sessions, with higher baseline concentrations observed in the evening, suggesting a potential circadian influence on irisin secretion.